Eksperimen Beton Mutu Tinggi Berbahan Fly Ash Sebagai Pengganti Sebagian Semen - Adibroto, Fauna; Suhelmidawati, Etri; Zade, Azri Azhar Musaddiq (Jurnal Ilmiah Rekayasa Sipil, 2018)
Various research in concrete sector has been done as an effort to increase quality of concrete, materials and method, materials technology and implementation techniques obtained from the results of the experiments and experiments are intended to answer the increasing demands on the use of concrete and overcome the constraints that often occur in the implementation of work in the field. One way to increase the strength of concrete is to use a cement replacement that is fly ash.The purpose of this research is to know the influence of partial cement replacement effect with fly ash to the concrete compressive strength, in order to be applicated for rigid pavement in road design. The variations of composition in the addition of fly ash is 0%, 10%, 12.5%, 15%, 20% and 25% of the weight of cement. Concrete compressive strength is 40 MPa and tested at 7 days and 28 days. This research tested concrete with cylinder test object (diameter 150 mm and height 300 mm) with 30 sample and consist of 6 variation. From this research, optimum compressive strength at 10% variation is 30,770 MPa. The lowest compressive strength is in the 25% variation with 20,046 MPa.The highest compressive strength obtained from the research is 30.770 Mpa.